Development and application of a gas chromatography method for simultaneously measuring H2 and CH4 in hydrothermal plume samples. (14th September 2015) - Wang, Hu; Zhou, Huaiyang; Yang, Qunhui; Lilley, Marvin D.; Wu, Jialin; Ji, Fuwu
Abstract: A robust, simple and efficient gas chromatography (GC) method is presented for determining H2 and CH4 concentrations simultaneously in water samples. The GC system consists of one detector (pulsed discharge helium ionization detector—PDHID), two columns in two ovens, respectively, and two 2‐position‐6‐port purge valves. In this method, H2 and CH4 in water samples were first extracted into the headspace of syringes, then injected into the GC system. Both H2 and CH4 were detected by a PDHID. The separation of CH4 from O2 and N2 in seawater is achieved by switching the O2 and N2 out of the carrier gas flow at the appropriate time window. H2 and CH4 concentrations in water samples collected from hydrothermal plumes at the Southwest Indian Ridge were determined successfully using this method.